Involvement of sphaeractinomyxon in the life cycle of mugiliform-infecting Myxobolus (Cnidaria, Myxosporea) reveals high functionality of actinospore morphotype in promoting transmission. Issue 12 (29th October 2020) - Rocha, Sónia; Rangel, Luís F.; Casal, Graça; Azevedo, Carlos; Rodrigues, Pedro; Santos, Maria J.
Abstract: Four new actinospore types belonging to the sphaeractinomyxon collective group (Cnidaria, Myxosporea) are described from the coelomic cavity of a marine Baltidrilus sp. (Oligochaeta, Naididae) inhabiting a northern Portuguese estuary. Host identification supports the usage of marine oligochaetes, namely of the family Naididae Ehrenberg, 1828, as definitive hosts for myxosporeans inhabiting estuarine/marine environments. The absence of mixed infections in the host specimens analysed is suggested to reflect the influence of host-, parasite- and environmental-related factors regulating myxosporean–annelid interactions. Molecular analyses matched the SSU rDNA sequences of three of the four new types with those of mugiliform-infecting Myxobolus spp., namely Myxobolus mugiliensis and a Myxobolus sp. from flathead grey mullet Mugil cephalus, and Myxobolus labrosus from thicklip grey mullet Chelon labrosus . These results directly link, for the first time, the sphaeractinomyxon collective group to a myxospore counterpart, further confirming their previously hypothesized specific involvement in the life cycle of myxobolids that infect mullets. Acknowledging this life cycle relationship, the functionality of the sphaeractinomyxon morphotype is suggested to have been decisive for the evolutionary hyperdiversification of the genus Myxobolus in mullets. Unlike other actinospore morphotypes, sphaeractinomyxon lack valvular processes, which implies a limited capability for buoyancy. Considering the benthic-feeding nature of mullets, this feature is most likely crucial in promoting successful transmission to the vertebrate host.